Reclaiming Indigenous Voice and Vision - Battiste, Marie. (UBC Press, 2000)
This book seeks to clarify postcolonial Indigenous thought beginning at the new millennium. It represents the voices of the first generation of global Indigenous scholars and converges those voices, their analyses, and their dreams of a decolonized world.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé